Optimization of microalgae cultivation and CO2 capture in a three-stage bubble column photobioreactor: Evaluation of control strategies - Emmanuel Yahaya; Yeo, Wan Sieng; Jobrun Nandong (Elsevier, 2025)
Global energy consumption is rising and worries about the depletion of fossil fuels and unchecked carbon dioxide (CO2) emissions make the switch to sustainable energy sources urgent. Due to their fast growth rates with high CO2 fixation, efficient nutrient removal from wastewater such as palm oil mill effluent, and lower cultivation area needs compared to traditional energy crops, microalgae, known for their adaptability, present a viable renewable energy alternative. To maximize microalgae growth in a photobioreactor system and specifically target the capture of high CO2 emissions from waste flue gases in the palm oil industry, this study focuses on evaluating Proportional-integral (PI) control strategies for such a purpose. The results show that algal productivity and CO2 capture efficiency depend critically on flue gas flow rate, CO2 inflow molar percentage, and higher dissolved oxygen (DO) levels. The hindering factors on algae growth are the elevated DO levels, highlighting the necessity of an efficient control strategy to reduce the generated DO in the medium. One such strategy’s implementation resulted in up to 75 % CO2 capture efficiency, or a 2 % CO2 molar fraction in the headspace, along with significant algal growth and specific productivity, suggesting possible uses in the generation of biodiesel or biobutanol. The microalgae-specific productivity and the carbon capture efficiency were better balanced by including control techniques to lower DO levels. The study highlighted the importance of creating customized control systems to maximize the delicate opposing trends between CO2 capture and microalgae production in sustainable energy applications.